Fostering Educational Excellence: Strategic Total Quality Leadership in Enhancing Institutional Performance within Islamic Secondary Education - Machdum Ibrohim Muwaffiqi; Mohamad Ahyar Ma’arif; Nur Fitri Amalia (Journal of Educational Management Research, 2026)
School leadership is a critical factor in improving educational quality by fostering effective management practices and sustainable institutional development. This study aimed to examine the implementation of quality-based leadership by exploring the principal’s strategies, the challenges encountered during implementation, and its contribution to enhancing students’ academic achievement and non-academic potential. A descriptive qualitative approach was employed, involving the principal, teachers, and educational staff as research participants. Data were collected through observations, interviews, and documentation and were analyzed using the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. The findings revealed that quality improvement was achieved through strengthening a quality culture, implementing academic supervision, enhancing teachers’ professional competencies, and optimizing academic and extracurricular programs. The implementation process faced several challenges, including limited facilities and infrastructure, an underdeveloped quality culture, variations in teachers’ competencies, and insufficient institutional funding. Despite these constraints, quality-based leadership contributed to improving instructional quality, strengthening student discipline, increasing learning motivation, and fostering students’ academic and non-academic achievements. These findings imply that sustainable quality-oriented leadership is essential for promoting continuous school improvement and strengthening institutional effectiveness.